Emerging roles of cancer-associated histone mutations in genomic instabilities - Yadav, Priyanka; Jain, Ronit; Yadav, Rajesh Kumar (Frontiers in Cell and Developmental Biology, 2024)
Epigenetic mechanisms often fuel the quick evolution of cancer cells from normal cells. Mutations or aberrant expressions in the enzymes of DNA methylation, histone post-translational modifications, and chromatin remodellers have been extensively investigated in cancer pathogenesis; however, cancer-associated histone mutants have gained momentum in recent decades. Next-generation sequencing of cancer cells has identified somatic recurrent mutations in all the histones (H3, H4, H2A, H2B, and H1) with different frequencies for various tumour types. Importantly, the well-characterised H3K27M, H3G34R/V, and H3K36M mutations are termed as oncohistone mutants because of their wide roles, from defects in cellular differentiation, transcriptional dysregulation, and perturbed epigenomic profiles to genomic instabilities. Mechanistically, these histone mutants impart their effects on histone modifications and/or on irregular distributions of chromatin complexes. Recent studies have identified the crucial roles of the H3K27M and H3G34R/V mutants in the DNA damage response pathway, but their impacts on chemotherapy and tumour progression remain elusive. In this review, we summarise the recent developments in their functions toward genomic instabilities and tumour progression. Finally, we discuss how such a mechanistic understanding can be harnessed toward the potential treatment of tumours harbouring the H3K27M, H3G34R/V, and H3K36M mutations.